Prevalence of filarial parasites in domestic and stray cats in Selangor State, Malaysia - Nazeh, M. Al-Abd; Zurainee, Mohamed Nor; Mustafa, Kassim; Marzida, Mansor; Abdulelah H., Al-Adhroey; Romano, Ngui; Sinnadurai, Sivanandam (Elsevier B.V, 2015)
Objective: To determine the prevalence of the filarial parasites,ie.,Brugia malayi, Brugia, Brugia pahangi(B. pahangi), Dirofilaria immitisandDirofilaria repens (D. repens) in domestic and stray cats. Methods: A total of 170 blood sample were collected from domestic and stray cats and examined for filarial worm parasites in two localities, Pulau Carey and Bukit Gasing, Selangor State, Malaysia. Results: The overall prevalence of infection was 23.5% (40/170; 95% CI = 17.4–30.6). Of this, 35% (14/40; 95% CI = 22.1–50.5) and 50% (20/40; 95% CI = 35.2–64.8) were positive for single B. pahangi nd D. repens, respectively. The remaining of 15% (6/40; 95% CI = 7.1–29.1) were positive for mixed B. pahangi and D. repens. In addition, 75% of the infected cats were domestic, and 25% were strays. No Brugia malayi and Dirofilaria immitis was detected. Eighty-four cats were captured at Pulau Carey, of which 35.7% (30/84) were infected. Among the cats determined to be infected, 93% (28/30; 95% CI = 78.7–98.2) were domestic, and only 6.7% (2/30; 95% CI = 19.0–21.3) were strays. Conversely, the number of infected cats was three times lower in Bukit Gasing than in Pulau Carey, and most of the cats were stray. Conclusions: B. pahangi and D. repens could be the major parasites underlying filariasis in the study area. Adequate prophylactic plans should be administrated in the cat population in study area.